Dynamic Interactions between Carbon and Energy Prices in the U.S. Regional Greenhouse Gas Initiative Region - Kim, Man-Keun; Lee, Kangil (International Journal of Energy Economics and Policy, 2015)
Numerous studies have investigated the dynamic interrelationship between carbon emission trading market and energy markets. Previous studies focused on the European Union Emissions Trading Scheme ascertain that carbon market and energy markets are closely attached, and find that electricity market is the main driver of the system. Our research on U.S. Regional Greenhouse Gas Initiative (RGGI) using Lag Augmented Vector Autoregression reveals that the RGGI market and electricity market in the region are tied but not strongly, unlike the EU-ETS. This loose relationship between the two markets might be explained by the recent weak carbon credit demand stemming from fuel switching and low electricity demand. Another finding is that natural gas is the main driver of the RGGI system, which is possibly due to from the recent shale gas boom. Keywords: Carbon emission trading; Lag Augmented Vector Autoregression; Regional Greenhouse Gas Initiative JEL Classifications: C32; Q52; Q53